Key skills development at firm level in regional perspective - case study for Romania - Vasilica Ciuca; Cristina Lincaru; Gabriela Tudose; Speranţa Pîrciog; Liliana Grecu; Ion Stegăroiu (European Regional Science Association (ERSA), 2010)
In view to define the need for change in the knowledge economy perspective an important place is occupied by the key competences development. In the new global context, with the digital and knowledge economy emergence"company expects current and prospective employees to bring this set of skills to the workplace".(a- Learning for the 21st century) . Some key competences are already recognized with transversal value by the employers - the ability to think creatively and logically in order to identify, formulate and solve problems, the ability to synthesize information, the ability to develop new skills, applying knowledge to the new situations, communicating, collaborating, making decisions and included into the "learning skills" literature etc. Based on the results of the Survey applied at national level, representatively at region NUTS 2 level, in Romania in 2008, we try to develop the firm perspective regarding the demand for the key skills development in regional perspective on medium term. (a)***, Learning for the 21first Century, A Report and Mile Guide for 21st Century Skills, pg.7, www.21scienturyskills.org
Keywords: 330